Photocatalytic activity of nanoparticles synthesized by green process - Achouak Ben nouh; Ihssan Bendjeddou; Inas Slimani (Université of Eloued, 2025)
This study explores the green synthesis of zinc oxide nanoparticles (ZnO NPs) using an extract from the Sonchus wightianus plant, and evaluates their photocatalytic performance in degrading organic pollutants. The photocatalytic activity of the synthesized ZnO was tested against two model dyes: Methylene Blue and Rose Bengal. The results revealed good degradation efficiency, particularly for Rose Bengal, suggesting that the nature of the dye significantly influences the photocatalytic response. Factors such as dye structure, charge, and interaction with the ZnO surface played a key role. This study confirms the potential of Sonchus wightianus as a natural and efficient reducing and stabilizing agent for green nanoparticle synthesis. Furthermore, it demonstrates the applicability of the resulting ZnO NPs in the field of environmental remediation, especially in the photocatalytic degradation of hazardous organic dyes. تستكشف هذه الدراسة التوليف الأخضر لجزيئات أكسيد الزنك النانوية ) ZnO NPs( باستخدام مستخلص من نبات Sonchus wightianus ، وتقيّم أداءها التحفيزي الضوئي في تحليل الملوثات العضوية. تم اختبار النشاط التحفيزي الضوئي لجزيئات ZnO المؤلفة ضد صبغتين نموذجيتين: الميثيلين الأزرق و وردي البنغال. أظهرت النتائج كفاءة تحليل جيدة، خاصة لصبغة الروز بنغال، مما يشير إلى أن طبيعة الصبغة تؤثر بشكل كبير على الاستجابة التحفيزية الضوئية. لعبت عوامل مثل بنية الصبغة، شحنتها، وتفاعلها مع سطح ZnO دورًا رئيسيًا. تؤكد هذه الدراسة إمكانية استخدام Sonchus wightianus كعامل مختزل ومثبت طبيعي وفعال لتوليف الجزيئات النانوية الخضراء. علاوة على ذلك، تُظهر قابلية تطبيق جزيئات ZnO الناتجة في مجال المعالجة البيئية، خاصة في التحليل التحفيزي الضوئي للأصباغ العضوية الخطرة
Master's theses in chemical engineering.2025
Keywords: Green synthesis; zinc oxide; nanoparticles; Sonchus wightianus; photocatalytic degradation; dyes; التوليف الأخضر؛ أكسيد الزنك؛ الجزيئات النانوية ؛ Sonchus wightianus ؛التحليل التحفيزي الضوئي؛ الأصباغ.